The equation you need takes the form
y = mx + b, where m is the slope.
So let's find the slope first ...
slope = (2-1)/-3-(-6))
= 1/3
so we have y = (1/3)x + b
but (-6,1) lies on it,
1 = (1/3)(-6) + b
1 = -2 + b
b = 3
equation: y = (1/3)x + 3
I usually check by subbin in the point that I did not use to get b
for (-3,2)
LS = 2
RS = (1/3)(-3) + 3
= 2 = LS
My equation is correct
Please help me:
I need an equation in slope intercept form when I know these values(-6,1) (-3,2). Do I have to do another equation first?
1 answer